Marital Shocks and Women's Welfare in Africa - Djuikom, Marie Albertine (World Bank, Washington, DC, 2018)
Marital shocks are exceedingly common for women in Sub-Saharan Africa. The paper investigates whether women who have suffered a marital rupture experience lower welfare levels relative to married women in their first union. Conditional means for women's nutritional status are compared by marital status across 20 countries. Overall, the results indicate significantly lower nutritional status for Africa's widows and divorcees between ages 15 and 49. With some exceptions, this is found to be the case with country and household fixed effects and controls for HIV status. However, looking at country-specific associations underlines that disadvantage is by no means universal.